Opioid Modulation of Recurrent Excitation in the Hippocampal Dentate Gyrus - Terman, Gregory W. (J Neurosci, 2000)
κ opioid receptor activation inhibits granule cell-mediated excitatory neurotransmission in the hippocampal formation via a decrease in glutamate release from both perforant path and mossy fiber terminals. We now report a third, anatomically and pharmacologically distinct site of such κ opioid inhibition within the hippocampus. Granule cell population responses to selective stimulation of an excitatory hilar pathway were decreased by the κ(1) opioid receptor agonist U69,593, an effect blocked by the κ(1) antagonist norbinaltorphimine. U69,593 also inhibited hilar path induced long-term potentiation (LTP) of granule cell responses. LTP in this pathway was also blocked by the NMDA receptor antagonist d-2-amino-5-phosphonovalerate, unlike granule cell mossy fiber LTP in CA3. The κ opioid peptide dynorphin is present in hilar mossy fiber collaterals. Ultrastructural analysis of these collaterals demonstrated dynorphin-containing vesicles in asymmetric synapses formed between axon terminals and granule cell dendrites, suggesting direct granule cell–granule cell connections. Evoked release of endogenous dynorphin within the hilus was effective in reducing hilar excitation of granule cells, although this release, in contrast to the release of dynorphin in the dentate molecular layer, was not dependent on L-type calcium channels. No hilar path excitation was observed in the absence of bicuculline, suggesting a strong GABA(A)-mediated inhibition of this pathway. However, hilar path activity could be seen after LTP, with or without bicuculline. Thus, κ opioids can inhibit granule cell recurrent excitation, likely via effects on excitatory mossy fiber collaterals. Such collaterals are thought to be important in mediating temporal lobe epilepsy.